School Selectivity, Peers, and Mental Health - Aline Bütikofer; Rita Ginja; Fanny Landaud; Katrine Vellesen Loken (Institute of Labor Economics (IZA), 2020)
Although many students suffer from anxiety and depression, and students often identify school pressure and concerns about their futures as the main reasons for their worries, little is known about the consequences of a selective school environment on students' physical and mental health. In this paper, we draw on rich administrative data and the features of the high school assignment system in the largest Norwegian cities to consider the long-term consequences of enrollment in a more selective high school. Using a regression discontinuity analysis, we show that eligibility to enroll in a more selective high school increases the probability of enrollment in higher education and decreases the probability of diagnosis or treatment by a general medical practitioner for psychological symptoms and diseases. We further document that enrolling in a more selective high school has a greater positive impact when there are larger changes in the student–teacher ratio, teachers' age, and the proportion of female teachers. These findings suggest that changes in teacher characteristics are important for better understanding the effects of a more selective school environment.
Keywords: 21; I26; I12; 330; selective high schools; higher education; health; mental health; peers